2016
DOI: 10.3389/fnbeh.2016.00042
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Visual Perceptual Learning Reveals Alterations in Neuronal Coding and Dendritic Spine Density in the Visual Cortex

Abstract: Visual perceptual learning (VPL) can improve spatial vision in normally sighted and visually impaired individuals. Although previous studies of humans and large animals have explored the neural basis of VPL, elucidation of the underlying cellular and molecular mechanisms remains a challenge. Owing to the advantages of molecular genetic and optogenetic manipulations, the mouse is a promising model for providing a mechanistic understanding of VPL. Here, we thoroughly evaluated the effects and properties of VPL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 78 publications
3
24
2
Order By: Relevance
“…It has been described that prolonged training near the individual visual threshold can improve vision, a phenomenon broadly referred to as perceptual learning (Schoups et al ., ; Wang et al ., ). Hence, we further investigated whether WD acted to facilitate perceptual learning and thereby sharpened visual acuity in the VWT experiments.…”
Section: Resultsmentioning
confidence: 97%
“…It has been described that prolonged training near the individual visual threshold can improve vision, a phenomenon broadly referred to as perceptual learning (Schoups et al ., ; Wang et al ., ). Hence, we further investigated whether WD acted to facilitate perceptual learning and thereby sharpened visual acuity in the VWT experiments.…”
Section: Resultsmentioning
confidence: 97%
“…For example, moment-to-moment changes in arousal level produce robust modulation of neuronal firing in V1 and alterations in perceptual ability [1][2][3][4] . Additionally, learning associations between sensory stimuli and behaviorally relevant outcomes can drive changes in neuronal structure, activity patterns, and perceptual ability [5][6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Performance on our head-fixed version of the acuity task was comparable to the more 84 commonly used 2-alternative forced-choice visual water task (Hosang et al, 2018;Prusky and 85 Douglas, 2004; Wang et al, 2016) in which mice are required to be in motion during acuity 86 assessment. In addition, similar to the visual water task, we found that daily participation in the 87 head-fixed acuity task resulted in improved spatial acuity.…”
Section: Introduction 64mentioning
confidence: 62%
“…This demonstrates that the mice 126 learned to lick in response to vertical gratings in general, and were capable of reporting the 127 presence of gratings when perceived. 128 Prusky and Douglas, 2004;Stephany et al, 2018;Wang et al, 2016). In addition to 133 performance accuracy, hit rate relative to the false alarm rate can be a useful indicator of 134 performance when the false alarm rate is low.…”
Section: Results 90mentioning
confidence: 99%
See 1 more Smart Citation